Le religioni della politica: Fra democrazie e totalitarismi - Gentile, Emilio (Gius.Laterza & Figli Spa, 2014)
La sacralizzazione della politica accade ogni volta che un'entità politica – la nazione, la democrazia, lo Stato, la razza, la classe, il partito, il movimento – è trasformata in una entità sacra, in un oggetto di devozione e di culto, ed è collocata al centro di un sistema di credenze, di simboli e di riti. Nascono allora le religioni della politica, che non si identificano con un unico tipo di ideologia e di regime: esse possono sacralizzare la democrazia o l'autocrazia, l'eguaglianza o la disuguaglianza, la nazione o l'umanità.
Keywords: essence of fascism; fascism; history / modern / 21st Century; political philosophy

Il sofisma economicista: intorno a Karl Polanyi - Caillé, Alain (sn, 2011)
KM translate: "The economic sophistry" and "The two meanings of" economic "", short writings by Karl Polanyi published here partially in a version taken from the French magazine MAUSS, represent a wonderful example of critical synthesis and set of depth of analysis, an analysis that comes to the conviction of the anthropological and social disaster caused not only by liberalism, but even more by the fallacy of an entire system of thought, economic science, which seeks to justify and support it. In support of the interesting pages of Polanyi, this book presents two contributions, respectively by Alain Caillé with Jean-Louis Laville and Jerome Maucourant, which, in addition to quickly presenting the intellectual biography of the Hungarian philosopher, clarify the extreme relevance of his critique of capitalism and the society of the markets. Polanyi emerges as an economist from the solid historical and anthropological foundations that, with his work, has been able to dismantle the apparently solid building of the classical economy to reveal its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century.
Keywords: business & economics; economic theory

Lavoro e società industriale. Da Adam Smith a Karl Polanyi - Rosa, Michele La; Rizza, Roberto; Zurla, Paolo (FrancoAngeli, 2006)
KM translate: The volume aims to provide a contribution to the knowledge of the ways of birth and consolidation of the sociological discourse on the economy, at work and their transformations connected to the process of industrialization. The goal, mainly educational, is pursued through the analysis of the contributions that Karl Marx, Emile Durkheim, Max Weber, Joseph Schumpeter, Karl Polanyi, Frederick Taylor and Elton Mayo have offered in this regard. The treatment of these authors, whose total or partial belonging to the sociological context is out of the question, was preceded by a brief analysis of others such as Adam Smith, Charles Babbage and Andrew Ure who, although not strictly belonging to this disciplinary area,
Keywords: DURKHEIM, Emile; MARX, Karl, 1818-1883; SMITH, Adam, 1723-1790; business & economics - labor; economic sociology; industrial revolution; industrialization; sociology of work